(untitled) (Research, Society and Development, 2023)
Circulatory shock is a clinical syndrome, characterized by the inability of the circulatory system to supply oxygen and nutrients to tissues in order to meet their metabolic needs. In its own characterization, it exposes an important relationship between metabolism and hemodynamics. The objective of this article is to relate the pathophysiology with the clinic of the patient affected by circulatory shock. This study is a narrative review with the purpose of discussing and describing pathophysiology with the clinic of the patient affected by circulatory shock. The database: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine) were used, with scientific data from March 2, 2023, with language restriction (Portuguese) and without restriction to the year of publication. Whenever there is a change in the functioning of the microvasculature, homeostatic mechanisms are mobilized with the aim of reestablishing a formidable circulation connection. Neural, humoral, and self-regulatory reflexes are activated. These compensatory mechanisms consist of phase I of shock which lowers arterial pressure. The analyzed studies allowed us to infer the strong relevance of the theme, when estimating the correlation between circulatory shock and its clinic.